Somatic embryogenesis of Polyscias fruticosa L. Harms via culturing ex vitro leaf explant - Nha Tram, To Thi; Yen, Truong Phi; Anh, Ton Trang; Tung, Hoang Thanh; My Ngan, Ha Thi; Tan Nhut, Duong (Vietnam Journal of Biotechnology, 2020)
Polyscisa fruticosa L. Harms is a medicinal plant containing alkaloids, glycosides, saponins, vitamins and phytosterols with many ginseng-like pharmacological effects such as strengthening fitness, increasing resistance and flexibility. However, the research on micropropagation on this plant is still limited. In this study, post-sterile leaf explants were used as initial culture material for the embryogenic- calli capable of producing somatic embryos (including morphology of somatic embryonic development stages), rooting and evaluation of acclimatization and growth at the greenhouse. The results showed that calli 0.5 cm gave optimum somatic embryos rate (75.53%) on MS medium supplemented with 100 mL/L of coconut water and 0.5 mg/L BA after 6 weeks of culture. The somatic embryo culture on MS medium added 0.1 mg/L Ki combined with 150 mL/L coconut water gave higher shoots regeneration rate (83.30%) and the number of shoots (6.30 shoots) than those cultured on other treatments after 8 weeks of culture. Besides, the in vitro plants were cultured on MS medium supplemented with 30 g/L sucrose and 100 mL/L coconut water for the highest number of roots (3.02 roots) and the ability to tame in the greenhouse (30 soil + 20 vermicomposts + 30 coconut husk + 20 husk ash) for high survival rate of 85.20%.